Environmental Taxes as a Path to a Green Transition - Huttmanová, Emília; Mikča, Radoslav (European Journal of Sustainable Development, 2024)
The integration of sustainability elements into all spheres of human activities is one of the primary initiatives of policymakers in individual European countries, but also in a broader international perspective. The transition towards more sustainable production-consumption models is now becoming a challenge for European countries. This shift is an essential part of the commitments and goals that the European Union has set itself in the medium and the long-term horizon. The future economic orientations of European countries will depend not only on the willingness and effort to use classical tools in the process of creating a green future, but especially on the level of knowledge of their appropriate implementation in practice. The paper is focused on the issue of the evaluation of selected economic instruments of environmental policy (environmental taxes) in the European area in the context of the transition to a green economy. The aim of the paper is to evaluate the use of taxes with an environmental aspect across European countries and to analyse the similarities in the process of their application towards green transformation. The need for a deeper knowledge and understanding of this area is essential in the context of the implementation of the Sustainable Development Goals in the countries involved in the 2030 Agenda.